Habitual dietary fibre intake and lifestyle characteristics in relation to functional constipation among adults in Malaysia - Siti Fatin Khadijah Mamat Ibrahim,; Asma’ Ali,; Khairil Shazmin Kamarudin,; Nor Hayati Ibrahim,; Azlin Shafrina Hasim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The World Health Organization (WHO) and the Food and Agriculture Organization (FAO) recommend consuming at least 25 g of dietary fibre daily. Adults with low fibre intake have an increased constipation risk. However, little research has been done on the habitual dietary fibre intake and lifestyle characteristics of functional constipation in Malaysian adults. Thus, the purpose of this study is to determine the dietary fibre intake, lifestyle characteristics, and functional constipation of adults in Malaysia, as well as the association between habitual dietary fibre intake, lifestyle characteristics, and functional constipation. About 318 adults between the ages of 18 and 59 participated and were asked to complete an online questionnaire consisting of three major parts. The components are as follows: i) the assessment of dietary fibre intake by using a semi-quantitative dietary fibre food frequency questionnaire; ii) the assessment of lifestyle factors; and iii) the determination of functional constipation via the Wexner Constipation Scoring System. SPSS 25 was used to analyse the data at a significance level of 0.05. The results indicated that the majority of adults consumed dietary fibre in amounts less than 25 g per day (84.6%). About 97.5% of adults have a healthy lifestyle, and only 2.8% of adults in this study faced constipation. There was no significant association between habitual dietary fibre intake and lifestyle characteristics (p=0.614) or between habitual dietary fibre intake and functional constipation among adults in Malaysia (p=0.147). Continued efforts are needed to increase dietary fibre intake among the adult population.